2004
DOI: 10.1158/1078-0432.ccr-04-0900
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a Correlation between the Presence of a Single Nucleotide Polymorphism in the Matrix Metalloproteinase 1 Promoter and Outcome in Patients of Chondrosarcoma

Abstract: Purpose: Increased levels of matrix metalloproteinase 1 (MMP-1) expression have been associated with poor outcome in chondrosarcoma. The existence of a single nucleotide polymorphism creating an Ets-binding site in the MMP-1 promoter may be one mechanism for elevated MMP-1 transcription. The aim of our study was to identify the prevalence of this single nucleotide polymorphism (SNP) in chondrosarcoma patients, to determine its correlation with disease outcome, and to discern whether it could serve as a prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
(28 reference statements)
1
17
0
2
Order By: Relevance
“…The study was judged to be of good quality if the total score was over 6, otherwise, of poor quality. The total score of most studies was over 6 except for four studies [28][29], [31], [33] (Table S2). The information of healthy controls was not provided in the four studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was judged to be of good quality if the total score was over 6, otherwise, of poor quality. The total score of most studies was over 6 except for four studies [28][29], [31], [33] (Table S2). The information of healthy controls was not provided in the four studies.…”
Section: Resultsmentioning
confidence: 99%
“…Different genotyping methods were used in these studies, including the classical polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in 21 of 33 studies [17][21], [23], [25][30], [39], [41][48], PCR-allele specific refractory mutation system analysis (ARMS) in 2 studies [7], [40], TaqMan assay in 4 studies [19], [22], [34], [37], PCR-sequencing in 6 studies [24], [31], [33], [35]–[36], [38], and PCR – fluorescent fragment analysis in 2 studies [28], [32].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified strong linkage between this polymorphism and several common malignancies, including colorectal (Ghilardi et al, 2001;Hinoda et al, 2002;Zinzindohoue et al, 2005;Elander et al, 2006), endometrial (Nishioka et al, 2000), lung (Zhu et al, 2001), and ovarian (Kanamori et al, 1999) cancers and melanoma (Rutter et al, 1998;Tower et al, 2002). Polymorphisms in the promoter of MMP-2 (Miao et al, 2003), MMP-3 (Ghilardi et al, 2002), and MMP-7 (Zhang et al, 2005) have also been associated with increased susceptibility to the development of cancer, and to poorer prognosis, but these associations have not been found in all studies (Lei et al, 2002;Wenham et al, 2003;Fong et al, 2004;Krippl et al, 2004;Zinzindohoue et al, 2005).…”
mentioning
confidence: 99%
“…An approach decreasing the ability of invasion and metastasis may facilitate the development of effective adjuvant therapy. In the processing of chondrosarcoma invasion and metastasis, the degradation of extracellular matrix (ECM) and the components of the basement membrane caused by the concerted action of proteinases, such as matrix metalloproteinases (MMP), cathepsins, and plasminogen activator, is a critical step in tumor invasion and metastasis [3,[5][6][7][8] . Among these enzymes, MMP-2 and MMP-9 degrade most components of the ECM directly and deeply involved in cancer invasion and metastasis [7,9] .…”
Section: Introductionmentioning
confidence: 99%